'Labour and new social movements in a globalising world system': the future of the past - Peter Waterman (Labor History Vol. 46, No. 2, May 2005, pp. 195-207, 2005)
A new set of questions [is] being created by a changing present. Questions about who constitutes the working class, about how fragmented and divided groups of workers have organised, issues about workplace and community and the democratisation of unions and state policies are assuming centre stage. As the contours of the present shift, it is becoming possible to look back from new perspectives.